Reticular Formation Connections Underlying Horizontal Gaze: The Central Mesencephalic Reticular Formation (cMRF) as a Conduit for the Collicular Saccade Signal - Wang, Niping; Perkins, Eddie; Zhou, Lan; Warren, Susan; May, Paul J. (Frontiers in Neuroanatomy, 2017)
The central mesencephalic reticular formation (cMRF) occupies much of the core of the midbrain tegmentum. Physiological studies indicate that it is involved in controlling gaze changes, particularly horizontal saccades. Anatomically, it receives input from the ipsilateral superior colliculus and it has downstream projections to the brainstem, including the horizontal gaze center located in the paramedian pontine reticular formation (PPRF). Consequently, it has been hypothesized that the cMRF plays a role in the spatiotemporal transformation needed to convert spatially coded collicular saccade signals into the temporally coded signals utilized by the premotor neurons of the horizontal gaze center. In this study, we used neuroanatomical tracers to examine the patterns of connectivity of the cMRF in macaque monkeys in order to determine whether the circuit organization supports this hypothesis. Since stimulation of the cMRF produces contraversive horizontal saccades and stimulation of the horizontal gaze center produces ipsiversive saccades, this would require an excitatory cMRF projection to the contralateral PPRF. Injections of anterograde tracers into the cMRF did produce labeled terminals within the PPRF. However, the terminations were denser ipsilaterally. Since the PPRF located contralateral to the movement direction is generally considered to be silent during a horizontal saccade, we then tested the hypothesis that this ipsilateral reticuloreticular pathway might be inhibitory. The ultrastructure of ipsilateral terminals was heterogeneous, with some displaying more extensive postsynaptic densities than others. Postembedding immunohistochemistry for GABA indicated that only a portion (35 %) of these cMRF terminals are GABAergic. Dual tracer experiments were undertaken to determine whether the superior colliculus provides input to cMRF reticuloreticular neurons projecting to the ipsilateral pons. Retrogradely labeled reticuloreticular neurons were predominantly distributed in the ipsilateral cMRF. Anterogradely labeled tectal terminals were observed in close association with a portion of these retrogradely labeled reticuloreticular neurons. Taken together, these results suggest that the superior colliculus does have connections with reticuloreticular neurons in the cMRF. However, the predominantly excitatory nature of the ipsilateral reticuloreticular projection argues against the hypothesis that this cMRF pathway is solely responsible for producing a spatiotemporal transformation of the collicular saccade signal.